7
$\begingroup$

I met with a multiple choice question,

Q. Let $E\subset M \subset \Bbb R^n$, where $M$ is a measurable (Lebesgue) set with $m(M)<\infty, $ then $E$ is measurable if

($m^*$ denotes the Lebesgue outer measure)

  1. $m(M)=m^*(E)+m^*(M\backslash E)$.

  2. $m(M)=m^*(E)+m^*(M\cap E)$.

  3. $m(M)=m^*(E)+m^*(M \triangle E)$, $\triangle$ denotes the symmetric difference.

  4. $m(M)=m^*(E)+m^*(M\cap E^c)$.

Caratheodory criterion says '$E$ is measurable if and only if $m^*(A)=m^*(A \cap E)+m^*(A \cap E^c)$ for all $A \subseteq \Bbb R^n$'. Thus, here I can see the measurability of $E$ implies the statements of First, Third and Fourth options (which are exactly the same). But how can we make a necessary and sufficient statement using the condition 'being a subset of a measurable set $M$'?

$\endgroup$

1 Answer 1

4
$\begingroup$

I'll do the proof for $1$.

I'll denote set difference by "$-$" for easier typing.

There exists a $G_{\delta}$ set $G$ such that $M-E\subset G $ and $m^{*}(M-E)=m(G)$ (I am assuming you know that Borel sets are measurable).

Then $M-E\subset M\cap G\subset G$ and hence $m^{*}(M-E)\leq m(M\cap G)\leq m(G) = m^{*}(M-E)\implies m^{*}(M-E)=m(M\cap G)$ .

As $M\cap G$ is measurable we have by Caratheodory cut condition on $M\cup G$ with $M$

$M\cap(M\cap G)= M\cup G$ and $M\cap(M\cap G)^{c}=M-G$

So $m(M)=m(M\cup G)+m(M-G)=m^{*}(M-E)+m(M-G)$ .

Now $m^*(M-E)=m(G)$ and we have the following claim that if $E$ is measurable and $F$ is any set then $m^{*}(E\cup F)+m^{*}(E\cap F)=m(E)+m^{*}(F)$ (You can prove this by using Cut condition on $E\cup F$ and $ F$ and is a standard result if you already know it. It is widely used in probability) . Now using this result for $E\subset F$ and $F-E$ to get $m^{*}(E\cup(F-E))+m^{*}(E\cap(F-E))=m^{*}(F)+m^{*}(\emptyset)=m(E)+m^{*}(F-E)$

Hence we have for $E$ measurable and $E\subset F$ that $m^{*}(F)=m(E)+m^{*}(F-E)$

Thus we can apply this to have $m(M)-m^{*}(M-E)=m^{*}(E)$ and this would mean $m^{*}(E)=m(M-G)$

Thus we have a measurable set $M-G$ whose measure equals the outer measure of $E$ and $m^{*}(E)<\infty$ .

This means that $m^{*}(E-(M-G))=m^{*}(E)-m^{*}(M-G)=0$ and hence $E-(M-G)$ is of measure $0$ and hence measurable.

This means $E=(E-(M-G))\cup (M-G)$ is measurable.

$\endgroup$
4
  • $\begingroup$ The equation $m^{*}(E-(M-G))=m^{*}(E)-m^{*}(M-G)=0$ is not well clear for me. How can we justify the additivity of $m^*$ on the sets $E-(M-G)$ and $M-G$ using the measurability of $M-G$? $\endgroup$
    – Messi Lio
    Jun 27 at 17:42
  • 1
    $\begingroup$ We are merely using the assumptions. We have $m^{*}(M-E)=m(G)$ . And $m(M)-m^{*}(M-E)=m(E)$. Hence So $m(M)-m(G)=m^{*}(E)$ and hence $m(M-G)=m^{*}(E)$ $\endgroup$ Jun 27 at 17:57
  • 1
    $\begingroup$ Now $M-G$ is a measurable set and as I said in the claim that if $E$ is measurable(and of finite measure) and $F$ is ANY set then $m^*(F-E)+m(E)=m^{*}(F)$. $\endgroup$ Jun 27 at 18:00
  • $\begingroup$ Thanks a lot Sir $\endgroup$
    – Messi Lio
    Jun 28 at 1:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.